86.6k views
0 votes
How do I solve x(3x-2)=(3x+1)(x-2)?

2 Answers

2 votes
First you simplify and combine like terms. Then you subtract 4x from both sides, leaving you with -2x = -1. Divide both by -2x, giving you the final of x = 1/2!!!
How do I solve x(3x-2)=(3x+1)(x-2)?-example-1
User RacerNerd
by
4.7k points
6 votes

x(3x - 2) = (3x + 1)(x - 2)

3x^2 - 2x = 3x^2 - 6x + x - 2

3x^2 - 2x = 3x^2 - 5x - 2

-2x = -5x - 2

-2x + 5x = -2

3x = -2

x = -2/3

hope this helped xx

User Kumar Elubandi
by
5.4k points